PROJECT ADMINISTRATION MANAGEMENT FOR KAYA PRODUCTION - Ubaydah Syawaltore; Rikip Ginanjar (President University, 2021)
Abstract—Projectmanagementisthekeytoneatcompany administration. The companywill grow in numbers andhire more workers and gain more projects. This system will helpthe company to manage, monitor, and track the progress of theirproject. It will help them get a better administration systemdashboard and be more productive to gainmore projects. Thissystem will allow them to track the progress from the beginningwhen a project starts, such as pitching follow-up to the executionprogress and the final billing reminder. A traditional method suchas writing manually in a digital notepad or file folder will bereplaced by this system since the old method may confuse if thecompany employee forgets to update the manual notepad. Thevision of the system will be beneficial when the company grows innumber later on more prominent.